751Investigation of the obesity paradox in kidney cancer: mystifying association or myth?. (2nd September 2021) - Heath, Alicia; Clasen, Joanna; Riboli, Elio; Scelo, Ghislaine; Muller, David
Abstract: Background: An "obesity paradox" has been reported in kidney cancer, whereby obesity is a risk factor, yet appears to be associated with better survival. To evaluate this paradox, we investigated the association between pre-diagnostic adiposity and renal cell carcinoma (RCC) incidence and mortality. Methods: Using data from 363, 521 men and women in the European Prospective Investigation into Cancer and Nutrition (EPIC), Cox regression models yielded confounder-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for RCC incidence and mortality in relation to BMI modelled continuously and using restricted cubic splines. RCC-specific and all-cause mortality were evaluated among cases. Results: During a mean follow-up of 14.9 years, 936 incident RCC cases were identified, 383 of whom died (278 due to RCC). Each 5 kg/m 2 increment in BMI was associated with 27% and 46% higher RCC incidence and mortality (HRs=1.27, 95% CI 1.18-1.37 and 1.46, 95% CI 1.28-1.66, respectively). Comparing a BMI of 35 with 22 kg/m 2, HRs for RCC incidence and mortality were 1.88 (95% CI 1.54-2.30) and 2.37 (95% CI 1.68-3.35), respectively. Among RCC cases, HRs per 5 kg/m 2 increment in BMI were 1.22 (95% CI 1.07-1.41) for RCC-specific mortality and 1.18 (95% CI 1.04-1.34) for all-cause mortality. Similar, positive linear associations were evident for waist circumference and waist-to-hip ratio. Conclusions: Obesity was associated with increased RCC incidence and mortality, and worse prognosis among cases. Key messages: The kidney cancer-obesity paradox does not appear to be real. Higher adiposity is associated with an increased risk of incident and fatal RCC.